Implementasi Profil Pelajar Pancasila dalam Pembelajaran PKn di Sekolah Dasar - Muhammad Oky Fauzi; Erindita Kirani; Nayla Azmi Mafaza; Nata Via Ramadan (Prosiding Konferensi Ilmiah Dasar, 2026)
This study aims to describe the implementation of the Pancasila Student Profile in Civic Education (PKn) learning at the elementary school level, identify the supporting and inhibiting factors, and formulate strategies to optimize its implementation. This research employed a qualitative descriptive approach through a literature review by analyzing relevant scientific articles and previous studies. The collected data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings indicate that the implementation of the Pancasila Student Profile has been integrated into Civic Education learning through student-centered learning activities, collaborative discussions, problem-solving, school habituation programs, and the Strengthening Pancasila Student Profile Project (P5). The success of its implementation is influenced by teachers' competence, school culture, adequate learning facilities, and collaboration among schools, families, and communities. However, several challenges remain, particularly differences in teachers' understanding of the Merdeka Curriculum and the integration of Pancasila values into classroom practices. Therefore, strengthening teacher competence and stakeholder collaboration is essential to optimize character education in elementary schools.